LITERATURE REVIEW: CHEMICAL CONTENT AND PHARMACOLOGICAL ACTIVITY OF KERSEN LEAF (Muntingia calabura L.) - Sari Sumarni; Asman Sadino; Sri Adi Sumiwi (Universitas Muhammadiyah Magelang, 2022)
Kersen (Muntingia calabura L.) is known as a plant that is often used as a tree to absorb air pollution and shade on the roadside. Low economic value and public knowledge about the benefits of cherry as a medicinal and food ingredient is still minimal. The part that can be used as a medicinal ingredient comes from cherry leaves. The purpose of this review article is to provide information related to the chemical content and pharmacological activity of cherry leaves that can treat various diseases. The method used in making this article review is a literature study. The literature sources in this article review were obtained from national journals and international journals published in the last 10 years (2010-2020), which were carried out online through the search engines Google Scholar, Pubmed, and NCBI, using the keywords "Kersen leaves", "Activities cherry leaf", "Pharmacological activity of Muntingia calabura", "Chemical content of cherry leaf", "Muntingia calabura L.". Journals that enter the inclusion criteria are national and international journals that discuss the pharmacological activity and chemical content of cherry leaves, journals published in the last 10 years (2010-2020), and journals in full text. The chemical constituents contained in cherry leaves are flavonoids, saponins, tannins, and terpenoids. Cherry leaves are scientifically proven to have several pharmacological activities as antidiabetic, antioxidant, antibacterial, anthelmintic, antihyperlipidemic, and anti-inflammatory.